1971
DOI: 10.1042/bj1210591
|View full text |Cite
|
Sign up to set email alerts
|

Purification of ribonuclease T1 by diethylaminoethylcellulose chromatography

Abstract: A procedure is described for isolating the enzyme ribonuclease T(1) from Takadiastase, an extract of the mould Aspergillus oryzae. It involves an initial concentration of the enzyme by adsorption on DEAE-cellulose followed by gradient elution. Later the enzyme is chromatographed on the same adsorbent with an eluent of constant composition. Yields of 350-380mg of ribonuclease T(1) from 500g of Takadiastase were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…This activity probably results from a minor contamination by nuclease Si (Ando, 1966) and could be removed by heating concentrated enzyme solutions at pH 6.5 to 100°for 5 min; a slight precipitate formed during this treatment which was removed by filtration. The specific activity of all the ribonuclease T, preparations agreed with that determined previously (Fields et al, 1971) and was not affected by the heat treatment. The concentration of ribonuclease Ti was determined spectrophotometrically using an extinction coefficient of 2.1 X 104 m-1 cm-1 at 278 nm (Egami et al, 1964).…”
Section: Methodssupporting
confidence: 87%
“…This activity probably results from a minor contamination by nuclease Si (Ando, 1966) and could be removed by heating concentrated enzyme solutions at pH 6.5 to 100°for 5 min; a slight precipitate formed during this treatment which was removed by filtration. The specific activity of all the ribonuclease T, preparations agreed with that determined previously (Fields et al, 1971) and was not affected by the heat treatment. The concentration of ribonuclease Ti was determined spectrophotometrically using an extinction coefficient of 2.1 X 104 m-1 cm-1 at 278 nm (Egami et al, 1964).…”
Section: Methodssupporting
confidence: 87%
“…Indeed, certain low-molecular-mass proteins are known to behave anomalously on SDS/PAGE [14]. For examples, ribonuclease A (13.7 kDa), ribonuclease T 1 (11.1 kDa) and the heavy chain of aspergillopepsin II (18.3 kDa) were reported to give molecular masses of 18.5 kDa (35 % overestimated) [14], 18.0 kDa (62 % overestimated) [15] and 33.0 kDa (80 % overestimated) [16] respectively on SDS/PAGE. The molecular mass of 23 kDa estimated by gel filtration is somewhat lower than the theoretical value of 33.4 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…To surmount this complication, we adapted a column-based method to purify fungal T1 and T2 RNases by binding them to an agarose column coupled with guanosine monophosphate (GMP) (Fields et al, 1971). We found that cell wall digesting enzymes readily passed through GMP columns, while the contaminating RNases remained stuck to the column.…”
Section: Enzyme Purification Is Necessary For Maintaining Rna Qualitymentioning
confidence: 99%